Translating the Symptom Screening in Pediatrics Tool (SSPedi) into French and among French-speaking children receiving cancer treatments, evaluating understandability and cultural relevance in a multiple-phase descriptive study. Issue 4 (9th April 2020) - Larouche, Valérie; Revon-Rivière, Gabriel; Johnston, Donna; Adeniyi, Oluwatoni; Giannakouros, Panagiota; Loves, Robyn; Tremblay, Jenna-Lee; Plenert, Erin; Dupuis, Lee; Sung, Lillian
Abstract : Objectives: Symptom Screening in Pediatrics Tool (SSPedi) is a validated approach to measuring bothersome symptoms for English-speaking and Spanish-speaking children with cancer and paediatric haematopoietic stem cell transplantation (HSCT) recipients. Objectives were to translate SSPedi into French, and among French-speaking children receiving cancer treatments, to evaluate understandability and cultural relevance. Methods: We conducted a multiphase, descriptive study to translate SSPedi into French. Forward translation was performed by four medical translators. After confirming that back translation was satisfactory, we enrolled French-speaking children with cancer and paediatric HSCT recipients at four centres in France and Canada. Primary and secondary outcome measures: Understandability was evaluated by children themselves who self-reported degree of difficulty, and by two adjudicators who rated incorrectness. Assessment of cultural relevance was qualitative. Participants were enrolled in cohorts of 10. Results: There were 30 children enrolled. Participants were enrolled from Marseille (n=10, 33%), Ottawa (n=1, 3%), Quebec City (n=11, 37%) and Toronto (n=8, 27%). No child reported that it was hard or very hard to complete French SSPedi in the last cohort of 10 participants. Changes to the instrument itself were not required. After enrolment of 30 respondents, the French translation of SSPedi was considered finalised based on self-reported difficulty with understanding, adjudicated incorrect understanding and cultural relevance. Conclusions: We translated and finalised SSPedi for use by French-speaking children and adolescents receiving cancer treatments. Future work should begin to use the translated version to conduct research and to facilitate clinical care.